Response to fluorophenylalanine by sensitive and resistant strains of Neurospora crassa - B. G. DeBusk; A. G. DeBusk (Fungal Genetics Reports, 1965)
Response to fluorophenylalanine by sensitive and resistant strains of Neurospora crassa